'Demand' for culture and 'allied' industries: policy insights from multi-site creative economy research. Issue 6 (19th September 2021) - Cunningham, Stuart; McCutcheon, Marion; Hearn, Greg; Ryan, Mark David
ABSTRACT: This paper draws policy insights from the first comparative analysis of multiple hotspots of regional cultural and creative activity across Australia. Focussing on the state of Queensland, it provides three interlinked findings relevant to international cultural policy debates. The first – municipal agency – goes to the crux of the value of studying small regions. We examine the degree to which Cairns, an isolated, small regional city, can exercise effective cultural agency in a tripartite system of government, demonstrating that policy ambition and asset management at the local level can deliver outsized cultural infrastructure benefits through a focus on demand from the local community. The second further illuminates the question of demand for cultural infrastructure as a critical enabler, in conjunction with allied infrastructure, in a very remote, distressed community–the Central West region. Cultural tourism's surprising prominence as support for mainstream tourism on the Gold Coast, an international mecca for surf, sand and sun, is the third example, deepening the significance of allied industry connectivity. Drawing on fieldwork conducted in 2019, the trend data and analysis offered here will be significantly impacted by the global COVID-19 pandemic of 2020.